Who Will Benefit from Charged-Particle Therapy? - Kim, Kyung Su; Wu, Hong-Gyun (Cancer research and treatment, 2021)
Charged-particle therapy (CPT) such as proton beam therapy (PBT) and carbon-ion radiotherapy (CIRT) exhibit substantial physical and biological advantages compared to conventional photon radiotherapy. As it can reduce the amount of radiation irradiated in the normal organ, CPT has been mainly applied to pediatric cancer and radioresistent tumors in the eloquent area. Although there is a possibility of greater benefits, high set-up cost and dearth of high level of clinical evidence hinder wide applications of CPT. This review aims to present recent clinical results of PBT and CIRT in selected diseases focusing on possible indications of CPT. We also discussed how clinical studies are conducted to increase the number of patients who can benefit from CPT despite its high cost.